The Impact of Foreign Debt on Economic Growth: An Analysis from Jasser Auda's Maqashid al-Shariah Perspective - Wardhani, Jayanti Sukma; Fadhillah, Anessa (Economica: Jurnal Ekonomi Islam, 2024)
This study aims to analyze the impact of foreign debt on economic growth from the perspective of Jasser Auda’s Maqashid al-Syariah framework. The research adopts a quantitative approach, utilizing secondary time-series data spanning 11 years (2010–2021), sourced from the Central Government's Ministry of Finance Foreign Debt Statistics Report and the Ministry of Trade’s GDP Report. The analysis methods applied include the Vector Autoregression (VAR) technique, variance decomposition analysis, and Granger Causality test, all conducted via E-Views 10. This study employs a purposefulness and openness approach to examine the unidirectional relationship between foreign debt and economic growth. Results reveal a long-term unidirectional relationship between economic growth variables and foreign debt, evidenced by an F-statistic probability exceeding the 5% threshold (>0.05). This indicates that increased economic growth in a country is partly driven by foreign debt.